PENERAPAN MODEL PEMBELAJARAN RECIPROCAL SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR MENULIS TEKS BERITA - Indri Widiastuti; Mayong Mayong; Azis Azis (Fakultas Teknik Universitas Negeri Makassar, 2023)
This study aims: (1) Describe the results of learning to write news texts by applying the reciprocal learning model in cycle I for class VIII students of SMP Negeri 1 Bone-Bone; (2) Describe the results of learning to write news texts by applying the reciprocal learning model in cycle II for class VIII students of SMP Negeri 1 Bone-Bone. This research is a classroom action research. The results of this study indicate that there is an increase in student learning activeness from cycle I to cycle II which also affects the increase in student learning outcomes. The results of increased learning in terms of the process are marked by an increase in student activity in implementing the results of observations of the activities of teachers and students in cycle I and students in cycle II. The improvement in terms of learning outcomes in writing news texts was marked by the average score of students in cycle I was 73, and the average value of students in cycle II was 84. Thus the application of the reciprocal learning model